Estimating inert gas bubbling from simple SCUBA diving parameters - Fichtner, Andreas (2021)
Inert gas bubbles frequently occur in SCUBA divers' vascular systems, eventually leading to decompression accidents. Only in professional settings, dive profiles can be adjusted on individual basis depending on bubble grades detected through ultrasonography. A total of 342 open-circuit air dives following sports diving profiles were assessed using echocardiography. Subsequently, (Eftedal-Brubakk) bubble grades were correlated with dive and individual parameters. Post-dive cardiac bubbles were observed in 47% of all dives and bubble grades were significantly correlated with depth (r=0.46), air consumption (r=0.41), age (r=0.25), dive time (r=0.23), decompression diving (r=0.19), surface time (r=- 0.12). Eftedal-Brubakk categorical bubble grades for sports diving with compressed air can be approximated by bubble grade = (age*50-1 - surface time*150-1+maximum depth*45-1+air consumption*4500-1)2 (units in years, hours, meter, and bar*liter; R2=0.31). Thus, simple dive and individual parameters allow reasonable estimation of especially relevant medium to higher bubble grades for information on relevant decompression stress after ascent. Echo bubble grade 0 is overestimated by the formula derived. However, echo might fail to detect minor bubbling only. The categorical prediction of individual decompression stress with simple bio and dive data should be evaluated further to be developed towards dive computer included automatic ex-post information for decision-making on individual safety measures.